2022
DOI: 10.1111/mms.12978
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and behavioral responses of tagged beluga whales (Delphinapterus leucas) to ships in the Pacific Arctic

Abstract: Arctic marine mammals face a multitude of challenges linked to climate change, including increasing anthropogenic noise from ship traffic. The beluga whale (Delphinapterus leucas), a predominately Arctic endemic cetacean, relies heavily on acoustic communication, with documented overlap between their vocalizations and hearing range and ship noise. Some belugas migrate through areas with the highest levels of ship traffic in the Pacific Arctic and exposure to ship noise is highly probable. Here, we document the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Different species of marine megafauna were not evenly protected by marine parks, with whale sharks found more frequently within moderate exposure areas in marine parks. This occurrence of whale sharks in areas with high shipping densities was also observed in Womersley et al (2022), and could be due to a lack of avoidance mechanisms of these sharks, as in some whales (McKenna et al 2015), although avoidance behaviours have been observed in odontocetes (Martin et al 2022). Although being strongly dependent on vessel design, reduced shipping speeds have been successful at lowering The movement patterns of marine giants suggest that they are exposed to shipping at over a third of the locations where tags recorded positions.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Different species of marine megafauna were not evenly protected by marine parks, with whale sharks found more frequently within moderate exposure areas in marine parks. This occurrence of whale sharks in areas with high shipping densities was also observed in Womersley et al (2022), and could be due to a lack of avoidance mechanisms of these sharks, as in some whales (McKenna et al 2015), although avoidance behaviours have been observed in odontocetes (Martin et al 2022). Although being strongly dependent on vessel design, reduced shipping speeds have been successful at lowering The movement patterns of marine giants suggest that they are exposed to shipping at over a third of the locations where tags recorded positions.…”
Section: Discussionmentioning
confidence: 80%
“…limited fishing v. exclusion zones); however, the areal extent of these subclassifications is often smaller than the exposure footprint of vessels that may transit adjacent to these zones (10 km in this study, with whales elsewhere showing avoidance behaviours been previously identified as a threat to these environments (Grech et al 2013). Often, the primary impact of shipping is considered to be port construction and management, and, to some degree, vessel strikes and pollution ( >30 km from ships; Martin et al 2022), with few of these zones (preservation zones in the Great Barrier Reef) explicitly excluding vessel transit. Marine park zoning should, therefore, explicitly include restrictions on large-vessel operation in addition to current restrictions, or design buffer zones to limit the effects of shipping on otherwise highly protected zones of interest.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings corroborate previous studies showing that bowhead whales do not tend to react to vessels performing standard operations at distances beyond 20 km. This result differs from the other two species of endemic Arctic cetaceans, beluga (Delphinapterus leucas) and narwhal (Monodon monoceros), which are known to exhibit strong avoidance reactions to vessels at farther distances (13 -50 km; Finley et al 1990;Martin et al 2022). Beluga and narwhal are gregarious odontocetes with different hearing sensitivities and social structures compared to bowhead whales, but specifically why beluga and narwhal show stronger avoidance reactions than bowheads remains unknown (Jefferson et al 1993;Ridgway et al 2001;Mooney et al 2018;Southall et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…There have been numerous studies documenting negative effects of underwater anthropogenic noise on marine species, with the greatest research focus on marine mammals (e.g., PAME 2019; Southall et al 2019;Duarte et al 2021). For Arctic marine mammals, underwater noise from vessels has been linked to acoustic masking (Pine et al 2018) and behavioural disturbance (Koski and Johnson 1987;Finley et al 1990;Martin et al 2022). Recent studies have begun to examine the potential overlap or exposure between some Arctic marine mammal populations and vessels or vessel noise (e.g., Reeves et al 2014;Halliday 2020b;Halliday et al 2018Halliday et al , 2021Halliday et al , 2022aHalliday et al , 2022bHauser et al 2018;Martin et al 2022).…”
Section: Introductionmentioning
confidence: 99%